Research on low productivity and logging evaluation of coalbed methane wells: a case study of the Baode block - Zhang, Jin-Hai; Li, Zhen; Li, Ying-Liang; Guo, Hong-Qiang; Hao, Rui; Pei, Yang (Frontiers in Earth Science, 2026)
In this work, we analyzed the causes of low productivity in coalbed methane (CBM) wells by considering the Baode block as a case study. In addition to investigating the reasons for low productivity in mature CBM wells, we developed logging interpretation methods to reassess and tap the remaining potential of such wells to revitalize existing resources. Given the development status of the Baode block, which is characterized by a high proportion of mature wells, rapidly declining production, and low wellhead pressure, we integrated logging, fracturing, well testing, production testing, and production dynamic data in this study to summarize the causes of low productivity. Furthermore, we established a well potential evaluation method for the mature wells in Baode block based on key indicators like the logging parameters, reservoir conditions, structural conditions, engineering conditions, and estimated gas production. The final outcomes of this work include identification of the potential well segments and their levels as well as stimulation plans for the identified wells. Application of the proposed method to the Baode block yielded significant results as follows: the average production increase in the stimulated potential wells exceeded 1,000 cubic meters per day, and the average single-well increase in the estimated ultimate recovery (EUR) exceeded 3 million cubic meters. Thus, the proposed approach provides valuable guidance for understanding the causes of low productivity in mature wells as well as enhancing their reserves and production.